The COVID-19 outbreak in Italy: perspectives from an orthopaedic hospital - Grassi, Alberto (Int Orthop, 2020)
PURPOSE: Italy is one of the more severely affected countries in the world by the recent COVID-19 outbreak. The aim of this report is to describe how COVID-19 affected the life and organization of one of the main orthopaedic hospitals of the country, and which measures were implemented to face the outbreak. METHODS: A personal interview has been conducted with four doctors involved in the management of COVID-19 outbreak in one of the main orthopaedic hospitals of Italy. RESULTS: Hospital was re-organized, elective surgeries were cancelled, and only trauma surgeries were allowed, together with oncologic and urgent cases. Since the number of cases among patients and healthcare workers increased, the hospital management responded not only with a massive testing campaign aimed at detecting contact histories but also with an additional testing campaign for asymptomatic healthcare workers. CONCLUSION: The main lection is that any actions should be quick and decisive, for 1 week during the COVID-19 epidemic could make the difference.